1963
DOI: 10.1126/science.142.3595.1065
|View full text |Cite
|
Sign up to set email alerts
|

Rhizomorph Production by Armillaria mellea Induced by Ethanol and Related Compounds

Abstract: Armillaria mellea produced abundant rhizomorphs when grown on a chemically defined medium containing ethanol at concentrations as low as 50 parts per million. In the absence of ethanol no rhizomorphs were formed. Rhizomorph production was also stimulated by I-propanol, isopropanol, and 1-butanol as well as by acetaldehyde (to a lesser extent). Potassium acetate had very slight stimulating effect, and methanol was completely ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…This study and previous studies (GARRAWAY 1970;WEINHOLD 1963;WEINHOLD and GARRAWAY 1966) indicated that several nutritional constituents must be present simultaneously in a synthetic medium for it to be maximally effective for thallus growth Comparison of 14C uptake and I4CO2 evolved by 7-day thalli^ of Armillaria mellea after 6 hours of incubation on media containing 14C-labelled glucose, fructose or sucrose with and without anthranilic acid and rhizomorph production by A. mellea. Key constituents include a carbon source, a nitrogen source, mineral salts, thiamine and an appropriate growth factor.…”
Section: Discussionmentioning
confidence: 93%
“…This study and previous studies (GARRAWAY 1970;WEINHOLD 1963;WEINHOLD and GARRAWAY 1966) indicated that several nutritional constituents must be present simultaneously in a synthetic medium for it to be maximally effective for thallus growth Comparison of 14C uptake and I4CO2 evolved by 7-day thalli^ of Armillaria mellea after 6 hours of incubation on media containing 14C-labelled glucose, fructose or sucrose with and without anthranilic acid and rhizomorph production by A. mellea. Key constituents include a carbon source, a nitrogen source, mineral salts, thiamine and an appropriate growth factor.…”
Section: Discussionmentioning
confidence: 93%
“…Boyle (1998) described that the nitrogen source in the medium was responsible for the mycelial growth increases of L. edodes because carbon sources that did not contain nitrogen sources were ineffective. Although it is well known that Armillaria grows vigorously and produces abundant rhizomorphs when cultured on medium that is supplemented with low-concentration alcohol (Weinhold 1963), it was reported that no extension of mycelia was observed in the absence of amino acids, and carbon sources were utilized for growth only when amino acids existed in the medium with alcohol (Weinhold and Garraway 1966). The amino acids in CNF-HWSF were not the direct promoting component; it seems that the amino acids have the possibility to support activation of promoting components.…”
Section: Discussionmentioning
confidence: 98%
“…Isolates that produced very slow-growing, crusty cultures were transferred to cellophane sheets on 3% malt agar amended with 20 mg/mL ethanol to stimulate rhizomorph production (Weinhold 1963). Mycelia and rhizomorphs were scraped from the cellophane and used fresh or were stored at -20 8C in 1.5 mL microcentrifuge tubes until needed.…”
Section: Dna Extractionmentioning
confidence: 99%